Pelatihan Penggunaan Benih Bermutu untuk Meningkatkan Produksi Petani Talas di Situgede, Bogor - Eny Widajati; Ridwan Diaguna; Okti Syah Isyani Permatasari (Agrokreatif: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2023)
Bogor is one of the centers of taro production, but productivity is low. It was caused by the use of low-quality seeds. The use of good quality of seed will increase taro productivity and production. Good quality seeds were uniform in size, clean, free from other varieties, and had high viability (vigor). This training was aimed at capturing the taro farmer's condition, cultivation technique, and knowledge about good quality of seed. The training was conducted in KTD Saluyu from August to September 2022 and was attended by 25 farmers. Training activities included expert presentations, discussions, and interviews. Evaluation of farmer knowledge change was determined by pre- and post-tests, while the effectiveness of training activities was evaluated to improve its effectiveness in the future. Taro farmers were dominated by men, aged about 40–59 years old (58.3%) and more than 60 years old, and almost all of their education background was elementary school. Farmers cultivated taro by sharing profit land (58.3%), ownership land (33.3%), and rent land (8.3%). Taro production was dominated by less than 1 ton, the monoculture system about 66.7%, and intercropping about 33.3%. Planting material was by farmer own seed from the previous season because there were limited certified seeds. Farmer knowledge increased by about 45.8% (from 4.9 to 7.2). This training was held under good management, as shown by the training evaluation score of about 90%. This training requires that it be held more intensively and sustainably through intensive assistance in the field and a seed production demonstration.